Study of Vehicle Loading System Aboard a Ferry Boat Owned by Pt. Asdp on the Hunimua - Waipirit Route, Maluku Province in 2020 - Irwan Irwan; Yohan Wibisono; Muhammad Rusedky (IWTJ : International Water Transport Journal, 2021)
Hunimua’s Ferry Port is a Ferry Port that serves inter-island crossings within the province with the Hunimua - Waipirit route. Hunimua’s Ferry Port is managed by PT. ASDP Ship and Regulation of Transportation Minister Number 115 of 2016 Regarding the Obligation to Bind Vehicles to Crossing Transport Ships Indonesia Ferry (Persero) Ambon Branch. This study aims to: 1.) To determine whether the transportation at KMP. Rokatenda, KMP. Terubuk and KMP. Inelika 2020 is in accordance with the Regulation of Transportation Minister Number 115 of 2016 Regarding the Obligation to Bind Vehicles to Crossing Transport Ships and Regulation of Transportation Minister Number 30 of 2016 Concerning the Procedures for Transporting Vehicles Aboard the Ship 2.) To analyze the transportation and vehicle binding equipment requirements required by KMP. Rokatenda, KMP. Terubuk And KMP. Inelika, and 3.) To evaluate the loading of vihicles and needs of lashing officers required by KMP. Rokatenda, KMP. Terubuk And KMP. Inelika. Then to analyze this it is guided by the PM number 115 of 2016 Regarding the Obligation to Bind Vehicles to Crossing Transport Ships and the Regulation of Transportation Minister Number 30 of 2016 Concerning the Procedures for Transporting Vehicles Aboard the Ship. The analysis that will be used is the analysis of the transportation of the vehicle on the ship, the analysis of the distance between the vehicles, and the analysis of the vehicle binding officers. The results of this study are: 1) The loading of vehicles on the crossings on the Hunimua - Waipirit route is still not in accordance with the loading procedures that have been regulated in the the Regulation of Transportation Minister Number 115 of 2016 Regarding the Obligation to Bind Vehicles to Crossing Transport Ships. 2) The obligation to tie the vehicle (Lashing) on ​​the ferry on the Hunimua - Waipirit route is still not in accordance with the Regulation of Transportation Minister Number 30 of 2016 Concerning the Procedures for Transporting Vehicles Aboard the Ship. due to the absence of binding vehicles on the ship. 3) There was no lashing officer on board the Hunimua - Waipirit crossing so that the vehicle was not placed according to the rules.